Efek Kandungan Minyak Jarak pada Bahan Bakar Solar terhadap Konsumsi Bahan Bakar dan Emisi Jelaga Mesin Diesel - Firman Lukman Sanjaya; Syarifudin (Politeknik Negeri Cilacap, 2020)
Castor oil is an alternative fuel as a substitute for diesel fuel. The property that approaches diesel fuel makes jatropha oil help reduce fossil fuel dependence. Abundant raw materials and high cetane properties make castor oil widely used as fuel in diesel engines. This study aims to observe the consumption of fuel and soot emissions produced by diesel engines using a mixture of diesel fuel with castor oil content of 30%. Based on the results of experiments that have been carried out, fuel consumption and soot emissions have increased. The highest increase occurred in SJ30 fuel at 25% loading. Low heating value is a major cause of increased consumption and soot emissions.